Underweight, overweight or obesity, diabetes, and hypertension in Bangladesh, 2004 to 2018 - Nguyen, Phuong Hong; Tauseef, Salauddin; Khuong, Long Quynh; Gupta, Rajat Das; Billah, Sk Masum; Menon, Purnima; Scott, Samuel P. (2022)
Bangladesh is experiencing a nutrition transition with an increase in the double burden of malnutrition and non-communicable diseases (NCDs). This study sought to: 1) examine trends and differences in underweight, overweight/obesity, hypertension and diabetes by gender, area of residence, and wealth in Bangladesh from 2004 to 2018, 2) assess what factors contributed to changes in these outcomes.